Analysis of active alkaloids in the Menispermaceae family by nonaqueous capillary electrophoresis‐ion trap mass spectrometry. Issue 2 (18th December 2012) - Chen, Qinhua; Zhang, Juan; Zhang, Wenpeng; Chen, Zilin
<x xml:space="preserve">Abstract</x> A nonaqueous CE‐IT MS with a nanospray ionization interface method was developed for the identification and quantification of tetrandrine (TET), fangchinoline (FAN), and sinomenine (SIN) using berberine as internal standard. The TET, FAN, and SIN standard solutions were directly infused into IT‐MS for collecting MS1–3 spectra. The major fragment ions of analytes were confirmed and possible main cleavage pathways of fragment ions were studied. A bare fused‐silica capillary was used for separation of the analytes. A sheath liquid (50% aqueous methanol containing 0.2% acetic acid) to the capillary effluent with a nanoelectrospray ionization interface was added. Separation buffer comprised 80 mM solution of ammonium acetate, in a mixture of 70% methanol, 20% ACN, and 10% water, which also contained 1% acetic acid. The CE‐MS method was validated for linearity, sensitivity, accuracy, and precision, and then used to determine the content of the above components. The detection limits of TET, FAN, and SIN are 0.05, 0.08, and 0.15μg/mL, respectively. The precision was no more than 4.67% and the mean recovery of the analytes were 95.36–99.24%. This method was successfully applied to determine TET, FAN, and SIN in real samples radix Stephaniae tetrandrae and rhizomes of Menispermum dauricum.